PENERAPAN PEMIDANAAN KEPADA PELAKU YANG DENGAN SENGAJA TIDAK MELAPORKAN ADANYA TINDAK PIDANA NARKOTIKA - Daeli, Debora Grace (LPPM Universitas Nias Raya, 2025)
Narcotics are substances or drugs originating from plants or non-plants, both synthetic and semi-synthetic which can cause a decrease or change in consciousness, disappearance, reduction and elimination of pain and cause addiction. One of the narcotics crimes that has been examined and tried by the Jeneponto District Court is decision number 153/Pid.Sus/2019/PN.Jnp. The type of research used is normative legal research with approach methods, statutory approaches, case approaches and analytical approaches. Data collection was carried out using secondary data, which was obtained through library materials consisting of primary, secondary and tertiary legal materials. The data analysis used is descriptive quantitative data analysis and conclusions are drawn using a deductive method. Based on the research findings and discussion, it can be concluded that the application of punishment to perpetrators who deliberately do not report a narcotics crime (decision study number 153/Pid.Sus/2019/PN.Jnp), in terms of evidence it is clear that the elements in article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, where the threat is imprisonment and a fine. However, in the decision, the judge adjudicating the case only sentenced the perpetrator to prison for 7 (seven) months in prison, without imposing a fine. The author suggests to law enforcement agencies that the Panel of Judges who examine and decide on Narcotics criminal cases should be more careful in imposing sentences imposed on perpetrators of Narcotics crimes in accordance with applicable laws and regulations.